Maternal Exposure to Steroid, Unknowing by Taking Medicine from Religious Ammil for Birth of Boy and the Risk of Oral Cleft in Newborn (Medical Forum Monthly, 2024)
Objective: The aim of present study was to find out a relation between environmental factors (steroid) and formation of Cleft Lip and Palate (CLP) by comparing the cases of CLP with controls.Study Design: Convenient Sampling, Case control.Place and Duration of Study: The study was conducted at the Mayo Hospital Lahore, Children Hospital Lahore and Arif Hospital, Rrashid Latif Medical College from 1st January 2014 to 31st December 2014.Materials and Methods: It was a convenient sampling, case control study, one hundred cases of Cleft Lip and Palate newborns up to age of six months, in different Hospitals of Lahore, having facilities of treating CLP. Antenatal history was taken in first three months of pregnancy from mothers about, taking medicine from religious Ammil for birth of male baby.Results: The frequency of CLP was found to be significantly higher in mothers who were taken medicine from religious Ammil for birth of boy (12% as compared to 7.4% of controls).Conclusion: Medicine taken from Religious Ammil during the first trimester of pregnancy resulted in increased frequency of CLP in newborns.